Psychiatric genetic counseling: A survey of Australian genetic counselors' practice and attitudes. Issue 2 (8th December 2022) - Isbister, Joanne; Sexton, Adrienne; Forrest, Laura E.; James, Paul; Dowty, James; Taylor, Jessica; Austin, Jehannine; Winship, Ingrid
Abstract: Genetic counseling plays a critical role in supporting individuals and their families' adaption to psychiatric conditions, addressing the multifactorial nature of these conditions in a personally meaningful and empowering way. Yet data related to the practice and attitudes of Australian genetic counselors about psychiatric genetic counseling (PGC) is limited. This survey investigated the practice of Australian genetic counselors, and their attitudes toward PGC. Genetic counselors ( N = 393) were invited to participate in an anonymous online survey between March and May 2022. Forty‐four genetic counselors (response rate = 11%) from Australia and New Zealand responded. No respondents practice in psychiatric genetics as their speciality area; most respondents do not see any patients where the primary indication is a personal and/or family history of psychiatric disorders (91%). Greater than half of respondents (56%) believed there was sufficient evidence to support PGC, and 64% enquire about personal and/or family history of psychiatric disorders, but only 25% provide genetic counseling on this topic. Most respondents do not feel confident providing risk assessments for psychiatric disorders (72%), while the majority expressed interest in attending specialist training (95%), and in incorporating PGC into future practice (77%). Australian genetic counselors would benefit from psychiatric genetic education and training, and establishment of specialized PGC services would address this gap in patient care, while providing opportunities for genetic counselors to gain skills and experience in PGC.